Concentration and Potential Ecological Risk of PAHs in Different Layers of Soil in the Petroleum-Contaminated Areas of the Loess Plateau, China - Wang, Di; Ma, Jing; Li, Hao; Zhang, Xingchang (International journal of environmental research and public health, 2018)
The three most representative areas of petroleum pollution on the Loess Plateau are the research subjects of this study. In this study, 16 priority polycyclic aromatic hydrocarbons (PAHs) were determined by the QuEChERS method combined with gas chromatography-tandem mass spectrometry (GC-MS/MS). The total concentrations of ∑16PAHs in top layer soils (0–10 cm), middle layer soils (10–30 cm), and bottom layer soils (30–50 cm) ranged from 1010.67 to 18,068.80, 495.85 to 9868.56 and 213.16 to 12,552.53 μg/kg, with an average of 5502.44, 2296.94 and 2203.88 μg/kg, respectively. The 3-ring and 4-ring PAHs were the most prominent components in all soil samples. Meanwhile, the average value of ∑16PAHs decreased with the depth, from 5502.44 μg/kg (0–10 cm) to 2203.88 μg/kg (30–50 cm). The PAHs levels in the studied soils were heavily polluted (over 1000 μg/kg) according to the Soils Quality Guidelines and 95% of PAHs come from petroleum sources. Moreover, the total of PAHs in petroleum-contaminated soils was assigned a high ecological risk level. Toxic equivalency quantities (TEQs) indicated that PAHs in petroleum-contaminated soils presented relatively high toxicity.